Effect of variations in the hitting point on the blade on performance of overshot water turbine - Duma, G.A.; Indah, A.B.R.; Sule, L.; Kondorura, K. (Universitas Mataram, 2025)
Water turbine is very important technology in producing electrical energy from renewable energy sources. Overshot turbine utilize specific gravity of water hit the blade and converts the potential energy of water into kinetic energy when the nozzle sprays water that hits the bucket and then passes it on to the transmission system becomes mechanical energy. This mechanical energy is converted into electrical energy by the generator. This research was carried out experimentally using five curved blades and an overshot turbine. The hitting point on blade distances are 0.13 m, 0.15 m, 0.17 m, 0.19 m, and 0.21 m and varying load, is 0.1 kg - 1.3 kg with constant discharge and head. The results obtained show that variations in hitting point on blades influence turbine power and turbine efficiency. The highest turbine power and efficiency for discharge of 0.0009 m3/s was obtained at hitting point of 0.13 m with load of 1 kg which produces 3.7888 watts of turbine power and efficiency is 25.05 %.